Professionals LLP limited liability regime for professionals: the business and ethical issues - Abd. Ghadas, Zuhairah Ariff (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Prior to the millennium era, it was an entrenched policy in Malaysia that certain professional are not allowed to carry out their businesses in the form of companies. As an example, lawyers in this country are only allowed to carry out business either through sole proprietorships or partnerships structure. In both business entities, the lawyers do not enjoy any protection of limited liability, either for professional negligence or business debts. The auditor and accountants are also confined with the same rule. Despite the rigidity of the governing rules, the law acknowledged the importance of the professionals to carry out their private practices and businesses. A new business entity in the Southeast region known as limited liability partnerships (LLP) has been introduced in Singapore in 2005; which allows the regulated professionals to enjoy limited liability without having to set up a company. In Malaysia, although it is not yet final, two consultation documents had been published by the Companies Commission of Malaysia (CCM); in 2003 and in 2008 indicated a high possibility for LLP to be offered in Malaysia. A draft bill of LLP had also been released by CCM in March 2009 to the professionals’ bodies such as Bar Council and MAICSA for feedback. This paper intends to highlight main attributes of LLP which allows professionals to enjoy limited liability while carrying out the business. It is contemplated that the move shall affect not only the liability regime but also the ethical issues and third parties protection. Main objective of this paper is to discuss the ethical issues which may arise out of the limited liability regime offered via LLP. Research methodologies adopted for this paper are statutory and case law analysis.